K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 7 2016

\(B=\left(\frac{2}{15}+\frac{5}{3}-\frac{3}{5}\right):\left(\frac{14}{3}-\frac{5}{2}\right)\)

\(B=\left(\frac{2}{15}+\frac{25}{15}-\frac{9}{15}\right):\left(\frac{28}{6}-\frac{15}{6}\right)\)

\(B=\frac{6}{5}:\frac{13}{6}\)

\(B=\frac{6}{5}.\frac{6}{13}\)

\(B=\frac{36}{65}\)

6 tháng 3 2023

địt con mẹ mày lên

 

6 tháng 3 2023

\(\dfrac{1}{3}\)-\(\dfrac{2}{15}\)+\(\dfrac{14}{15}\)=\(\dfrac{3}{15}\)-\(\dfrac{2}{15}\)+\(\dfrac{14}{15}\)

=\(\dfrac{13}{15}\)

26 tháng 8 2023

Bài 1:

a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)

\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)

\(\Rightarrow x=\dfrac{6}{7}\)

b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)

\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)

\(\Rightarrow x=\dfrac{1}{6}\)

26 tháng 8 2023

help me

16 tháng 12 2022

A= 2/5 - 1

= -3/5

B= -30/24 + 4/24 - 36/24 

= 31/12

16 tháng 12 2022

A = 3/7 x 2x7/3x5 - 3x6/7x3 x 7/6 = 2/5 - 3/3 = 2/5 - 5/5 = -3/5

B=1/6 - (5/4 + 3/2) = 1/6 -(5/4 + 6/4)= 1/6 - 11/4 = 2/12 - 33/12   = - 21/12

25 tháng 6 2016

a) \(\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}\right)+\frac{3}{5}:\left(-\frac{1}{3}-1\frac{1}{15}\right)\)

\(=\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}-\frac{2}{6}-1+\frac{1}{15}\right)\)

\(=\frac{3}{5}:\left(-\frac{1}{2}-1\right)\)

\(=\frac{3}{5}:\left(-\frac{3}{2}\right)\)

\(=-\frac{2}{5}\)

25 tháng 6 2016

b) \(\left(-\frac{3}{4}+\frac{5}{13}\right):\frac{2}{7}-\left(2\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)

\(=\left(-\frac{3}{4}+\frac{5}{13}-2+\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)

\(=\left(-\frac{1}{2}+1-2\right):\frac{2}{7}\)

\(=\left(-\frac{1}{2}-1\right):\frac{2}{7}\)

\(=-\frac{3}{2}:\frac{2}{7}\)

\(=-\frac{21}{4}\)

1 tháng 8 2016

a. \(\frac{9^{15}}{3^{14}.27^6}=\frac{3^{30}}{3^{32}}=\frac{1}{3^2}=\frac{1}{9}\)

b. \(\frac{14^5.8^3}{2^{10}.7^9}=\frac{2^5.7^5.2^9}{2^{10}.7^9}=\frac{2^{14}.7^5}{2^{10}.7^9}=\frac{2^4}{7^4}=\left(\frac{2}{7}\right)^4=\frac{16}{2401}\)

9 tháng 5 2020

-4/5 + 11/3 - 9/10       =(-4/5 + 11/3) -9/10              =43/15 -9/10        =59/30                                                                                                      5/6 + -7/15 - 13/30            =(5/6 + -7/15) -13/30                =11/30 - 13/30          =-1/15                                                                                                           CHÚC EM HỌC TỐT ^_^

25 tháng 4 2019

\(\frac{4}{5}\)\(\frac{1}{5}\)\(\frac{-2}{15}\)\(\frac{4}{5}\)\(\frac{1}{5}\)\(\frac{-15}{2}\)=\(\frac{4}{5}\) + \(\frac{-3}{2}\)\(\frac{-7}{10}\)

25 tháng 4 2019

b = \(\frac{-7}{12}\). (\(\frac{3}{11}\)\(\frac{-14}{11}\)) + \(\frac{5}{6}\)\(\frac{-7}{12}\). (-1) + \(\frac{5}{6}\)\(\frac{7}{12}\)\(\frac{10}{12}\)\(\frac{17}{12}\)

8 tháng 7 2023

|7 - \(\dfrac{3}{4}\)\(x\)| - \(\dfrac{3}{2}\) = \(\dfrac{1}{\dfrac{1}{2}}\)

|7 - \(\dfrac{3}{4}x\)|  - \(\dfrac{3}{2}\) = 2

|7 - \(\dfrac{3}{4}\)\(x\)| = 2 + \(\dfrac{3}{2}\)

|7 - \(\dfrac{3}{4}x\)| = \(\dfrac{7}{2}\)

\(\left[{}\begin{matrix}7-\dfrac{3}{4}x=\dfrac{7}{2}\\7-\dfrac{3}{4}x=-\dfrac{7}{2}\end{matrix}\right.\) 

\(\left[{}\begin{matrix}\dfrac{3}{4}x=7-\dfrac{7}{2}\\\dfrac{3}{4}=7+\dfrac{7}{2}\end{matrix}\right.\)

\(\left[{}\begin{matrix}\dfrac{3}{4}x=\dfrac{7}{2}\\\dfrac{3}{4}x=\dfrac{21}{2}\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=\dfrac{14}{3}\\x=14\end{matrix}\right.\)

8 tháng 7 2023

 5  - |\(x-3\)| = 5

       |\(x-3\)| = 5 - 5

      |\(x-3\)| = 0

      \(x-3\) = 0 

      \(x\) = 3